Students' Ability To Write Narrative Texts and Students' Reading Interest Through Video-Based Learning Media - Nesi Oktias Gita (International Journal of Contextual Science Education, 2026)
This research aims to determine the effect of video-based learning media on students’ ability to write narrative texts and their reading interest. The background of the study lies in the low literacy and writing performance among students due to monotonous learning approaches that rely heavily on textbooks. This study applied a quasi-experimental method involving two groups of elementary school students: the experimental group using video-based media and the control group using conventional methods. The novelty of this study lies in the integrated examination of both narrative writing ability and reading interest through the use of video-based learning media, which is still rarely explored simultaneously at the elementary education level. The data were collected through writing tests and reading interest questionnaires, analyzed using descriptive statistics and t-tests. The results show that video-based learning significantly enhances students’ narrative writing ability and stimulates reading interest through audio-visual engagement. The findings suggest that integrating video-based media can create a more interactive and motivating literacy learning environment and contribute to the development of innovative literacy instruction strategies.